King of scars - Bardugo, Leigh (Bardugo, Leigh. King of scars duology, 2019)
When the dark magical force within him challenges his effort to forge new alliances and build a defense against a new threat, Nikolai Lantsov, the young king of Ravka, embarks on a journey to his country's most magical places to vanquish it.